Expression pattern, ethanol-metabolizing activities, and cellular localization of alcohol and aldehyde dehydrogenases in human large bowel: association of the functional polymorphisms of ADH and ALDH genes with hemorrhoids and colorectal cancer - Chiang, Chien-Ping; Jao, Shu-Wen; Lee, Shiao-Pieng; Chen, Pei-Chi; Chung, Chia-Chi; Lee, Shou-Lun; Nieh, Shin; Yin, Shih-Jiun (Alcohol (Fayetteville, N.Y.), 2012)
Alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) are principal enzymes responsible for metabolism of ethanol. Functional polymorphisms of ADH1B, ADH1C, and ALDH2 genes occur among racial populations. The goal of this study was to systematically determine the functional expressions and cellular localization of ADHs and ALDHs in human rectal mucosa, the lesions of adenocarcinoma and hemorrhoid, and the genetic association of allelic variations of ADH and ALDH with large bowel disorders. Twenty-one surgical specimens of rectal adenocarcinoma and the adjacent normal mucosa, including 16 paired tissues of rectal tumor, normal mucosae of rectum and sigmoid colon from the same individuals, and 18 surgical mixed hemorrhoid specimens and leukocyte DNA samples from 103 colorectal cancer patients, 67 hemorrhoid patients, and 545 control subjects recruited in previous study, were investigated. The isozyme/allozyme expression patterns of ADH and ALDH were identified by isoelectric focusing and the activities were assayed spectrophotometrically. The protein contents of ADH/ALDH isozymes were determined by immunoblotting using the corresponding purified class-specific antibodies; the cellular activity and protein localizations were detected by immunohistochemistry and histochemistry, respectively. Genotypes of ADH1B, ADH1C, and ALDH2 were determined by polymerase chain reaction-restriction fragment length polymorphisms. At 33 mM ethanol, pH 7.5, the activity of ADH1C*1/1 phenotypes exhibited 87% higher than that of the ADH1C*1/*2 phenotypes in normal rectal mucosa. The activity of ALDH2-active phenotypes of rectal mucosa was 33% greater than ALDH2-inactive phenotypes at 200 μM acetaldehyde. The protein contents in normal rectal mucosa were in the following order: ADH1 > ALDH2 > ADH3 ≈ ALDH1A1, whereas those of ADH2, ADH4, and ALDH3A1 were fairly low. Both activity and content of ADH1 were significantly decreased in rectal tumors, whereas the ALDH activity remained unchanged. The ADH activity was also significantly reduced in hemorrhoids. ADH4 and ALDH3A1 were uniquely expressed in the squamous epithelium of anus at anorectal junctions. The allele frequencies of ADH1C*1 and ALDH2*2 were significantly higher in colorectal cancer and that of ALDH2*2 also significantly greater in hemorrhoids. In conclusion, ADH and ALDH isozymes are differentially expressed in mucosal cells of rectum and anus. The results suggest that acetaldehyde, an immediate metabolite of ethanol, may play an etiological role in pathogenesis of large bowel diseases.